A historical overview of nursing professional organisations in the interwar period in Poland - Przybek-Mita, Joanna (Nursing Problems / Problemy Pielęgniarstwa, 2016)
The interwar period in Poland was a time of rapid growth in the number of qualified healthcare workers, mainly doctors and certified nurses. Their earnings depended on factors such as qualifications, the popularity of the profession and professional specialty, position, gender, place of residence, and even nationality. In spite of their general education and high professional qualifications, nurses were treated as physical labourers. Their work time was unregulated and earnings were equivalent to the salary of lower hospital staff. Housing conditions, often dramatic, hampered normal rest and personal life for them. This situation contributed to the creation of the first nursing professional organisations. They were registered as societies and associations. Thus, scientific activity was simulated, although the main purpose of these professional organisations was to provide various forms of professional self-help and the struggle for improving the status of the profession in society. The purpose of this study is to present a historical overview of nursing professional organisations in the interwar period, mainly the Polish Association of Professional Nurses, the Association of Graduates at Czyste district in Warsaw, the Union of Social Nurses and the Independent Union of Certified Nurses. Their activity was associated with legal and professional success, mainly with the introduction of the Act on Nursing Profession. There were also the first nursing strikes, which were brutally suppressed and the movement was condemned as contrary to the principles of nurses’ professional ethics.